Judicial Preview: Pembaharuan Prosedur Verifikasi Konstitusionalitas Sebagai Wujud Harmonisasi Nilai Kepastian dan Keadilan Hukum - Albanna, Syedna Ahmad; Jumantoro, Tegar Raffi Putra; Cahaya, Budi Indra; Putra, Alejandro Yudhas Rangga; Shafarida, Moh. Affan Ghaffar (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The Indonesian legal system is still confronted with the antinomy between the values of legal certainty and justice. This can be seen from the numerous laws that have been annulled by the Constitutional Court (MK) due to their inconsistency with the constitution. This research aims to analyze the urgency of implementing the concept of Judicial Preview in Indonesia as a solution to the antinomy between the values of legal certainty and justice in the formation of legislation. This research uses a normative legal method and is conducted through conceptual and legal approaches. Through a legal approach, it is intended to analyze the problem of the high number of annulled laws by the Constitutional Court. This research also utilizes secondary data, such as laws. The data collection method is carried out through a literature study process that examines literature materials, such as scientific journals, books, and online websites. The research results indicate that Judicial Preview, as a mechanism for testing laws before enactment, can be a solution to prevent laws that are inconsistent with the constitution. Judicial Preview can provide legal certainty to the public that enacted laws will not violate their constitutional rights. Additionally, Judicial Preview can also help realize legal justice. The implementation of the Judicial Preview concept in Indonesia can be an effective solution to address the antinomy between the values of legal certainty and justice in the formation of legislation. By implementing Judicial Preview, it is hoped that higher quality laws, in line with constitutional values, can be created, providing legal certainty and justice for society.